Kepastian Hukum Rekomendasi MKDKI pada Penyidikan Perkara Dugaan Tindak Pidana oleh Tenaga Medis - Heru Iskandar; Y.A. Triana Ohoiwutun; Al Khanif (Lembaga Pengembangan Kinerja Dosen, 2024)
The global COVID-19 pandemic has disrupted the health sector, forcing countries to transform their health. In Indonesia, the response to this crisis was the issuance of a new health law, namely Law No. 17 of 2023. One of the updates is the provision that provides legal protection for medical personnel, namely in the process of criminal investigations against medical personnel, investigators must first request a recommendation from the authorized panel in disciplinary examinations, in this case, referring to the previous law, the Indonesian Medical Discipline Honorary Council (MKDKI). The recommendation determines whether the investigation can be continued or not based on the implementation of the professional practice of medical personnel, whether or not it is in accordance with professional standards, service standards, and standard operating procedures. The request for a recommendation from the panel must be received by the investigator no later than 14 days, and if it is more than that, the panel is considered to have approved the investigation of medical personnel. This is a polemic because for crucial decisions, namely assessing whether or not there is a violation of standards, only 14 days are given, while in reality the examination takes months. Finally, the research is presented to measure the legal certainty of the complaint examination procedure within the MKDKI, the legal certainty of the panel's recommendations regarding the continuation of the investigation process, and to reformulate provisions that are not yet fair in the process.